Pengembangan Bisnis Model Program Perkarangan Pangan Lestari (P2L) Berbasis Ekonomi Sirkular Pada Kegiatan Kampung Pangan Di Kota Tomohon - Wariki, Barce Andries Feriano; Laoh, Olly Esry Harryani; Purbopuspito, Joko (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2026)
The Sustainable Food Yard Program (P2L) within the "Kampung Pangan" (Food Village) initiative in Tomohon City has demonstrated success in increasing household food productivity and reducing stunting rates. However, the program's sustainability faces challenges regarding the economic value of commodities, the capacity for pure organic production, and the technical skills of the driving forces. In 2025, the Kampung Pangan Program was expanded with "Pangan Mandiri" (Independent Food) activities, which provide financial assistance and equipment to 32 farmer groups across Tomohon City. This study aims to formulate a development strategy for the P2L program by integrating the nine elements of the Business Model Canvas (BMC) and five components of the circular economy. The research method employed a descriptive qualitative and quantitative approach with purposive sampling of 48 respondents. Data were analyzed using the SWOT matrix, Quantitative Strategic Priority Management (QSPM), and farm income analysis. The results indicate that the Pangan Mandiri activities in Tomohon City fundamentally fulfill the elements of a business model. Recommended development strategies include agricultural extensification, enhancing organic vegetable production quality, improving plantation transportation infrastructure, and achieving independence in organic fertilizer production to mitigate chemical fertilizer scarcity. The implementation of this model is projected to increase family income by 5% annually and strengthen sustainable local food security.